2000
DOI: 10.1046/j.1365-2540.2000.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the phenotypic effects of B chromosomes in a natural population of Metagagrella tenuipes (Arachnida: Opiliones)

Abstract: Phenotypic effects of B chromosomes in a natural population of Metagagrella tenuipes (Arachnida: Opiliones) were studied. Mean number of Bs per individual in the population studied was 6.0, and remained stable during two successive summers of 1997 and 1998. In contrast to the number of B chromosomes, ratios between individuals possessing odd and those possessing even numbers of Bs changed during both collection seasons: the proportion of harvestmen with an even number of Bs decreased from June-July to October-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…3 together with data obtained in 1997 and 1998 at the same population (Gorlov and Tsurusaki, 2000a). In 1994, the number of Bs increased from August (2.7) to October (6.0).…”
Section: Seasonal Change Of the Number Of Bs At Yatsukami Populationsupporting
confidence: 57%
See 4 more Smart Citations
“…3 together with data obtained in 1997 and 1998 at the same population (Gorlov and Tsurusaki, 2000a). In 1994, the number of Bs increased from August (2.7) to October (6.0).…”
Section: Seasonal Change Of the Number Of Bs At Yatsukami Populationsupporting
confidence: 57%
“…0.0001). It is unlikely that the number of Bs differed between sexes in this generation, since it has been shown that the number of Bs does not differ between sexes, at least in subadults and younger adults just after the final molting (Tsurusaki, 1993;Gorlov and Tsurusaki, 2000a). Decrease of the number of Bs in embryos was also ascertained in additional rearing experiments using females from the same population in 1995 (Tables 1 and 2).…”
Section: Seasonal Change Of the Number Of Bs At Yatsukami Populationmentioning
confidence: 93%
See 3 more Smart Citations